Domestic hot and cold water consumption in households in Szczecin between 2006-2019 - Jaszewska, Marta; Szaflik, Władysław (Instal, 2020)
The article presents the results of studies on hot and cold water consumption by residents of several housing estates in Szczecin in the years 2006 – 2019. The average annual hot and cold water consumption in subsequent years was determined. They were compared with the average water consumption in several years in Poland. It turned out that in the subsequent years the amount of water intake in Poland in cities and villages was slowly approaching each other and in 2018 it was at a similar level. In the years 2006 – 2014 the total water consumption in the examined objects practically did not change. On average, it was about 96 [dm3/ (person day)]. From 2015 it began to grow and in 2019 it reached the value of about 109 [dm3/ (person day)]. The hot water consumption throughout the entire period was practically constant and amounted to about 40 [dm3/ (person day)].